Different microvascular alterations underlie microbleeds and microinfarcts. Issue 2 (14th June 2019) - van Veluw, Susanne J.; Scherlek, Ashley A.; Freeze, Whitney M.; ter Telgte, Annemieke; van der Kouwe, Andre J.; Bacskai, Brian J.; Frosch, Matthew P.; Greenberg, Steven M.
Abstract : Objective: Cerebral amyloid angiopathy (CAA) is characterized by the accumulation of amyloid β (Aβ) in the walls of cortical vessels and the accrual of microbleeds and microinfarcts over time. The relationship between CAA severity and microbleeds and microinfarcts as well as the sequence of events that lead to lesion formation remain poorly understood. Methods: We scanned intact formalin‐fixed hemispheres of 12 CAA cases with magnetic resonance imaging (MRI), followed by histopathological examination in predefined areas and serial sectioning in targeted areas with multiple lesions. Results: In total, 1, 168 cortical microbleeds and 472 cortical microinfarcts were observed on ex vivo MRI. Increasing CAA severity at the whole‐brain or regional level was not associated with the number of microbleeds or microinfarcts. However, locally, the density of Aβ‐positive cortical vessels was lower surrounding a microbleed compared to a simulated control lesion, and higher surrounding microinfarcts. Serial sectioning revealed that for (n = 28) microbleeds, both Aβ (4%) and smooth muscle cells (4%) were almost never present in the vessel wall at the site of bleeding, but Aβ was frequently observed upstream or downstream (71%), as was extensive fibrin(ogen) buildup (87%). In contrast, for (n = 22) microinfarcts, vascular Aβ was almost always observed at the core of the lesion (91%, p < 0.001) as well as upstream or downstream (82%), but few vessels associated with microinfarcts had intact smooth muscle cells (9%). Interpretation: These observations provide a model for how a single neuropathologic process such as CAA may result in hemorrhagic or ischemic brain lesions potentially through 2 different mechanistic pathways. ANN NEUROL 2019;86:279–292